Strain-Controlled Recombination in InGaN/GaN Multiple Quantum Wells on Silicon Substrates - Tao Lin; Zhi Yan Zhou; Yao Min Huang; Kun Yang; Bai Jun Zhang; Zhe Chuan Feng (Nanoscale Research Letters, 2018)
Abstract This paper reports the photoluminescence (PL) properties of InGaN/GaN multiple quantum well (MQW) light-emitting diodes grown on silicon substrates which were designed with different tensile stress controlling architecture like periodic Si δ-doping to the n-type GaN layer or inserting InGaN/AlGaN layer for investigating the strain-controlled recombination mechanism in the system. PL results turned out that tensile stress released samples had better PL performances as their external quantum efficiencies increased to 17%, 7 times larger than the one of regular sample. Detail analysis confirmed they had smaller nonradiative recombination rates ((2.5~2.8)×10−2 s−1 compared to (3.6~4.7)× 10−2 s−1), which was associated with the better crystalline quality and absence of dislocations or cracks. Furthermore, their radiative recombination rates were found more stable and were much higher ((5.7~5.8) ×10−3 s−1 compared to [9~7] ×10−4 s−1) at room temperature. This was ascribed to the suppression of shallow localized states on MQW interfaces, leaving the deep radiative localization centers inside InGaN layers dominating the radiative recombination.